2010
DOI: 10.1080/02699930903306181
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to genuine versus posed emotion specified in facial displays

Abstract: To link to this Article: DOI: 10.1080/0269993090330618

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
105
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 47 publications
(54 reference statements)
9
105
2
Order By: Relevance
“…The effect of reliable AUs on the identification of emotion is less conclusive than their effect on perceived intensity of the emotion and on perceived authenticity, which suggests that reliable AUs might be more important in the assessment of intensity, genuineness, and trustworthiness of internal states than in the classification of these states in emotion categories. It also indicates that perceivers' sensitivity to subtle differences between posed and genuine emotional displays (Gosselin et al, 2002;McLellan et al, 2010) may be related to the activation of a subset of facial movements. Thus, although both versatile and reliable AUs would work together to create emotional expressions, our results suggest that reliable AUs contribute to making them look more authentic and more intense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of reliable AUs on the identification of emotion is less conclusive than their effect on perceived intensity of the emotion and on perceived authenticity, which suggests that reliable AUs might be more important in the assessment of intensity, genuineness, and trustworthiness of internal states than in the classification of these states in emotion categories. It also indicates that perceivers' sensitivity to subtle differences between posed and genuine emotional displays (Gosselin et al, 2002;McLellan et al, 2010) may be related to the activation of a subset of facial movements. Thus, although both versatile and reliable AUs would work together to create emotional expressions, our results suggest that reliable AUs contribute to making them look more authentic and more intense.…”
Section: Discussionmentioning
confidence: 99%
“…be used by perceivers to discriminate between both types of expression (McLellan, Johnston, Dalrymple-Alford, & Porter, 2010). Previous research using acted emotional portrayals showed that facial movements that are expected in the expression of a given emotion are more frequently used in the portrayals than facial movements that are not expected to be present in that emotion (Gosselin, Kirouac, & Doré, 1995).…”
mentioning
confidence: 99%
“…First, we establish norms for many of the stimuli from two popular databases that are widely used in the literature, the Pictures of Facial Affect (PoFA; Ekman & Friesen, 1976) and the Radboud Faces Database (RaFD; Langner et al, 2010), and for the only published set (the McLellan faces; as provided to us, T. McLellan, personal communication, November 24, 2010; see also McLellan et al, 2010) where the actual emotional state of the displayer has been verified (by self-report) for emotions other than happiness.…”
Section: Study Aims: Development Of Norms and New Stimulus Setsmentioning
confidence: 99%
“…Although the focus has mostly been on happy expressions (Ekman & Friesen, 1982;Frank, Ekman, & Friesen, 1993; for a review, see Gunnery & Ruben, 2016), more recent work has begun to include a broader range of emotions, asking questions such as: Can adults discriminate genuineness in facial expressions other than happiness (e.g., sadness, fear, Electronic supplementary material The online version of this article (doi:10.3758/s13428-016-0813-2) contains supplementary material, which is available to authorized users. disgust; Douglas, Porter, & Johnston, 2012;McLellan, Johnston, Dalrymple-Alford, & Porter, 2010)? Can children do the same (sadness, fear; Dawel, Palermo, O'Kearney, & McKone, 2015)?…”
mentioning
confidence: 99%
“…The major part of CK+ and CK Enhanced datasets contains posed facial expressions that may considerably differ from the spontaneous ones [31]. Spontaneous expressions, which may differ in intensity, timing, and co-occurrence with other actions [32], [5], [2].…”
Section: Study On Au12/au14 Intensity Estimation On Spontaneous Datamentioning
confidence: 99%